Smart Design of Learning Media Innovation Module Based Character Education Technology - Oviensy, Vegia; Kustati, Martin; Nanasepriyanti; Zebua, Ali Marzuki; Kurnia, Asraf (Rayah Al-Islam, 2024)
The success or failure of a lesson, especially in Islamic religious education which focuses on character education is largely determined by the learning media used, in realizing this success a problem arises, namely the teacher is still monotonous in using learning media so that learning cannot be properly accepted by students. This is based on the results of a survey by researchers via Google form that 80% of students stated that educators tended to use the lecture system more in the learning process, 70% of students could not understand the subject matter only with notes given by the teacher, 95% preferred to learn using learning media, 97% of students agree to use multimedia so that learning is not boring. As well as the lack of development of learning media for the blind. During the Covid-19 pandemic, students tended to be closer to the digital world, this was based on survey data that 99% of students actively used social media during the pandemic, especially social media Tiktok, namely around 78% of students used Tiktok longer. Even Tiktok social media users have increased by around 14.3 million per month. Seeing these problems, the researchers created a new innovation Smart Module, an innovation of technology-based character education learning media, namely technology that can combine the virtual world with the real world at the same time and is equipped with braille letters that are used for normal students and people with visual impairments. This research uses the type of R&D with the Borg and Gall development model. Data collection techniques were carried out through observation, questionnaires, literature studies, documentation and trials and then analyzed using media expert validation analysis techniques, material expert validation analysis techniques and trial analysis techniques. The specific purpose of making this media is to find out whether the Smart Module is valid to use and how student learning outcomes are after using this module. The results of this study show that the Smart Module has a validity level of 92% and can improve student learning outcomes.